PERANCANGAN SISTEM INFORMASI KELENGKAPAN RESUME MEDIS DI RSIA HUMANA PRIMA BANDUNG - Pujirahayu, Dina Mardiana; Syahidin, Yuda; Hidayati, Meira (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2022)
Completeness of filling in a medical record is very important because medical records are written evidence, especially on a medical resume sheet. Medical Resume are often used for the benefit of BPJS claims, other insurance, and currently, claims of the covid-19 patient require a complete medical resume. As the result of the research conducted there are several problems regarding the completeness of the medical resume: 1). Reporting is done manually by checking one by one paper-based medical record, 2). Report that has not been made for 2 years, 3). There are many incomplete medical resumes. This study uses a qualitative method through a descriptive, and a data collection technique used is observation. To overcome the problems that occur regarding the completeness of medical resumes at RSIA Humana Prima Bandung, the author has a solution by making a Medical Resume Complete Information System Design using Microsoft Visual Studio 2010 and Microsoft Access 2010 as database. The development method used is the waterfall method.